Attachment-retained overdentures - ÖZKAN, YASEMİN; GÖZNELİ, RİFAT (Springer Nature, 2023)
Since attachment-retained dentures improve patients’ aesthetics and facilitate function, the attachments have become very satisfactory. However, the attachments are not preferred by many dental clinicians because of their high cost and technical difficulty. The attachments resist separation forces, which tend to move the denture away from the soft tissues (retention of the denture), provide periodontal support for the denture, transmit the forces of masticatory muscles on the denture to periodontium axially, distribute the forces, and stabilize and splint the supporting teeth. The most appropriate system is determined by the number, distribution, and location of the remaining natural teeth. Correct diagnosis and treatment planning ensures that the remaining teeth perform well over time to maintain adequate bone height and periodontal support. Tooth-supported overdenture (TSO) attachments are typically placed directly in the root or used in conjunction with a coping mechanism.
Keywords: Diş Hekimliği; Klinik Bilimler; Protetik Diş Tedavisi; Sağlık Bilimleri; Dentistry; Clinical Sciences; Prosthetic Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry